2015
DOI: 10.1074/mcp.m115.048967
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Recurrence and Survival for Triple-Negative Breast Cancer (TNBC) by a Protein Signature in Tissue Samples

Abstract: To date, there is no available targeted therapy for patients who are diagnosed with triple-negative breast cancers (TNBC). The aim of this study was to identify a new specific target for specific treatments. Frozen primary tumors were collected from 83 adjuvant therapynaive TNBC patients. These samples were used for global proteome profiling by iTRAQ-OFFGEL-LC-MS/MS approach in two series: a training cohort (n ‫؍‬ 42) and a test set (n ‫؍‬ 41). Patients who remains free of local or distant metastasis for a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…Overexpression of DP and TPS1 significantly altered the disease free survival and enhanced the risk of recurrence of TNBC patients. However, it was also reported that overexpression of TrpRS was associated with better disease free patient survival and lower risk of recurrence 98 . Another iTRAQ labelling based proteomics study identified several factors which have strong associations with molecular subtypes of breast cancer (fibronectin, alpha-2-macroglobulin (A2M), complement component-4-binding protein alpha (C4BPA) and complement factor-B).…”
Section: Triple-negative Breast Cancer (Tnbc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of DP and TPS1 significantly altered the disease free survival and enhanced the risk of recurrence of TNBC patients. However, it was also reported that overexpression of TrpRS was associated with better disease free patient survival and lower risk of recurrence 98 . Another iTRAQ labelling based proteomics study identified several factors which have strong associations with molecular subtypes of breast cancer (fibronectin, alpha-2-macroglobulin (A2M), complement component-4-binding protein alpha (C4BPA) and complement factor-B).…”
Section: Triple-negative Breast Cancer (Tnbc)mentioning
confidence: 99%
“…Both iTRAQ and TMT strategies have been broadly employed in cancer studies for drug discovery 49 , investigating cancer signaling 50 , as well as for investigating diagnostic and prognosis markers 51 . iTRAQ has also been employed to predict cancer recurrence and patient survival in triple negative breast tissue samples 52 . Although these approaches have shown merit, they are less accurate and sensitive compared with SILAC, as the tag is added at a later stage of the procedure, resulting in lower proteome coverage 53 .…”
Section: Quantitative Mass Spectrometry-based Proteomic Strategies Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome screening was performed using Affymetrix Human Genome U133 Plus 2.0 Arrays (Affymetrix, Santa Clara, CA) measuring over 54 000 transcripts representing over 20 000 human genes. These two methods have been fully described in previous works …”
Section: Methodsmentioning
confidence: 99%
“…In accordance to its anti‐angiogenic property, high tumour expression of TSP‐1 is correlated with increased patient survival in colon, lung, bladder, ovarian, cervical and gastric cancer . However, high tumour tissue TSP‐1 is also associated with decreased survival in patients with hepatocellular carcinoma, breast cancer and melanoma . Along with the observation that high VEGF in cancer is usually associated with worse prognosis and increased metastasis, it is very likely that certain types of cancer (eg breast cancer) may have developed compensatory mechanisms to counteract the anti‐angiogenic pathways activated by TSP‐1 .…”
Section: Conclusion and Future Considerationsmentioning
confidence: 99%